The Implementation of 3D Media and Interactive Video to Improve Maharah Kalam in Arabic Learning at Madrasah Tsanawiyah - Aida, Izzah Nur; Wulandari Wima, Annisa Eriska; Al Aly, Adif (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study aims to examine the application of 3D media integration and interactive videos in improving speaking skills (maharah kalam) of Madrasah Tsanawiyah students. The background of this study is the low ability of students in speaking Arabic due to monotonous learning methods and minimal interaction. The method used is qualitative with data collection techniques through interviews, classroom observations, and questionnaires. The research subjects consisted of teachers and students of class VIII MTs Miftahul Ulum Rambipuji Jember who were actively involved in this technology-based learning. The results showed significant improvement in vocabulary (from 58% to 86%), sentence structure (52% to 81%), and contex-tual application (47% to 79%). 3D media was shown to strengthen visual comprehension and linguistic context, while interactive videos encouraged active participation and better pronunciation through immedi-ate feedback. The findings indicate that an integrative approach between visual and interactive media can improve students' cognitive and affective aspects simultaneously. The study recommends wider implemen-tation of digital media in the Arabic curriculum as well as continuous teacher training to maximize the po-tential of technology in improving students' productive skills.